Vegetation Analysis in Areas Around The Landslides of Palopo City - Dewi Marwati Nuryanti; Liana Baharuddin; Witno witno; Andang Suryana Soma; Asriyanni Asriyanni; Srida Mitra Ayu (Universitas Andi Djemma Palopo, 2022)
The composition and structure of vegetation is one of the parameters that must be considered in forest planning activities. It can also be defined that the structure of vegetation as a result of spatial planning by the components of the stand and the life form of the vegetation which is described through the conditions of diameter, height, distribution in space, canopy diversity, and species continuity. In order to be able to withstand the occurrence of landslides, especially those in sloping areas, it is very important to analyze the vegetation to determine the composition and structure of vegetation types so that the forest is maintained (Fahrul, 2007). The purpose of this study was to determine vegetation in the existing area around the landslides in Palopo city. Research methods. The method of determining plots is purposive sampling, to find out vegetation and tree classification based on the growth rate of the method, namely by making observation plots and placing them by census at the top of 12 landslide points with a size of 20 m x 20 m for trees, 10 m x 10 m for poles, 5 m x 5 m for saplings and 2 m x 2 m for seedlings. The results obtained for the growth rate of trees found 35 species with the highest IVI Litsea sp 95.94%, the growth rate of poles found 28 species with the highest IVI Litsea sp 71.15%, the growth rate of saplings found 62 species with the highest IVI Cinnamomum camphora 45.62 %, and the level of seedlings found 51 species with the highest IVI Nephrolepis cordifolia 40.78%. The biodiversity index found a sapling growth rate with the highest H' value of 3.41 in the high species diversity category. Likewise the highest evenness index on saplings with an E' value of 0.59 is in medium level of evenness.